Empirical Modeling of Contagion : A Review of Methodologies - Dungey, Mardi; Fry, Renee; Gonzalez-Hermosillo, Brenda; Martin, Vance (Washington, D.C. : International Monetary Fund, 2004)
The existing literature suggests a number of alternative methods to test for the presence of contagion during financial market crises. This paper reviews those methods and shows how they are related in a unified framework. A number of extensions are also suggested that allow for multivariate testing, endogeneity issues, and structural breaks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet